Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 23

Queer(ing) Italo-Québécois Literature : QUESCREN Working Paper no. 8 - Canton, Licia (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
This paper explores the cultural production of Quebec English-language writers who function at the intersection of ethnicity and sexual identity: the LGBTQ+ and Italian community. We will introduce the writing of established and emerging literary artists: Steve Galluccio, Christopher DiRaddo, Liana Cusmano5 (aka BiCurious George), Vee DG (aka Vanessa Di Gregorio), Anthony Portulese and others. These writers are the children or grandchildren of Italian immigrants to Quebec, and they identify as members of the LGBTQ+ community.

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)